Improvements in transition times through the HIV cascade of care among gay and bisexual men with a new HIV diagnosis in New South Wales and Victoria, Australia (2012–19): a longitudinal cohort study. Issue 10 (October 2021) - van Santen, Daniela K; Asselin, Jason; Haber, Noah A; Traeger, Michael W; Callander, Denton; Donovan, Basil; El-Hayek, Carol; McMahon, James H; Petoumenos, Kathy; McManus, Hamish; Hoy, Jennifer F; Hellard, Margaret; et al.
Summary: Background: Most studies assessing the HIV care cascade have typically been cross-sectional analyses, which do not capture the transition time to subsequent stages. We aimed to assess the longitudinal HIV cascade of care in Australia, and changes over time in transition times and associated factors. Methods: In this longitudinal cohort study, we included linked data for gay and bisexual men (GBM) with a new HIV diagnosis who attended clinics participating in the Australian Collaboration for Coordinated Enhanced Sentinel Surveillance in New South Wales and Victoria between Jan 1, 2012, and Dec 31, 2019. We assessed three cascade transition periods: diagnosis to linkage to care (stage 1 transition); linkage to care to antiretroviral therapy (ART) initiation (stage 2 transition); and ART initiation to virological suppression (viral load ≤200 copies per mL; stage 3 transition). We also calculated the probability of remaining virologically suppressed after the first recorded viral load of less than 200 copies per mL. We used the Kaplan-Meier method to estimate transition times and cumulative probability of stage transition. Findings: We included 2196 GBM newly diagnosed with HIV between 2012 and 2019 contributing 6747 person-years of follow-up in our analysis. Median time from HIV diagnosis to linkage to care (stage 1 transition) was 2 days (IQR 1–3). Median time from linkage to care to ART initiation (stage 2 transition) was 33 days (30–35). Median time from ART initiation to first recorded virological suppression (stage 3 transition) was 49 days (47–52). The cumulative probability of ART initiation within 90 days of linkage to care increased from 36·9% (95% CI 32·9–40·6) in the 2012–13 calendar period to 94·1% (91·2–96·0) in the 2018–19 calendar period and cumulative probability of virological suppression within 90 days of ART initiation increased from 54·3% (48·8–59·3) in the 2012–13 calendar period to 82·9% (78·4–86·4) in the 2018–19 calendar period. 91·6% (90·1–93·1) of GBM remained virologically supressed up to 2 years after their first recorded virological suppression event. Interpretation: In countries with high cross-sectional cascade estimates such as Australia, the impact of treatment as prevention is better estimated using longitudinal cascade analyses. Funding: National Health and Medical Research Council Australia.